Financial Valuation Workbook : Step-by-Step Exercises and Tests to Help You Master Financial Valuation. - Hitchner, James R.; Mard, Michael J. (Hoboken : John Wiley & Sons, 2011)
The resource that cuts the learning curve in half for valuation professionalsNow valuation professionals can master almost every function for most valuation situations. The Financial Valuation Workbook, Third Edition guides readers through a complete business valuation with essential tools for quick reference. Updated and expanded chapter on The Process of Preparing a Valuation- Client Workflow Procedures from initial phone call to delivery of the reportExpanded case study and exercises with solutions and explanationsOver 300 exercises organized by major areas to increase the learning process.
Cover; Series; Title Page; Copyright; Dedication; About the Authors; Acknowledgments; Preface; Chapter 1: Valuation Case Study Exercises; Chapter 2: Valuation Case Study Exercises: Solutions and Explanations; Chapter 3: Financial Valuation: Applications and Models Companion Exercises and Test Questions; Chapter 4: ValTips; Chapter 5: Income Approach Valuation Process Flowchart; Chapter 6: Marketing, Managing, and Making Money in Valuation Services; Chapter 7: Practice Management Workflow Procedures; Chapter 8: Checklists; Index.
Print version record.
Keywords: Corporations -- Valuation; Corporations -- Valuation -- Handbooks, manuals, etc; Business enterprises -- Valuation; Business enterprises -- Valuation -- Handbooks, manuals, etc; Business enterprises -- Valuation -- Handbooks, manuals, etc; Corporations -- Valuation -- Handbooks, manuals, etc; Business; Electronic books